2017
DOI: 10.4172/2375-4508.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elevated LH: FSH Ratio on IVF Outcome, Comparing the Impacts of Different Triggering Medicines

Abstract: Objective: To study how elevated LH: FSH ratio influence IVF outcome in High response patients with different triggering medicines.Design: This study was observational study performed in Medcare Fertility Centre, Dubai, UAE, between April 2016 to July 2017.Patients: 81 high ovarian response women (AMH ≥ 4 ng/ml and LH/FSH ≥ 1). Main outcome:Measures the impact of high LH/FSH ratioo on IVF outcome in according to the triggering used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Researchers have recently reported that elevated Day-3 FSH:LH ra o correlates with [18][19] higher rates of cancella on in IVF-embryo transfer cycles. Based on few studies, one can use a day-3 FSH:LH or LH:FSH [20][21] ra o as predictor of ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have recently reported that elevated Day-3 FSH:LH ra o correlates with [18][19] higher rates of cancella on in IVF-embryo transfer cycles. Based on few studies, one can use a day-3 FSH:LH or LH:FSH [20][21] ra o as predictor of ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%